Cover Feature: Acid Hydrotropic Fractionation of Lignocelluloses for Sustainable Biorefinery: Advantages, Opportunities, and Research Needs (ChemSusChem 15/2021). Issue 15 (16th July 2021) - Zhu, Junyong; Chen, Liheng; Cai, Cheng
Abstract : The Cover Feature shows acid hydrotropic fractionation (AHF) of lignocellulosic plant biomass at atmospheric pressure, to result in cellulose‐rich water‐insoluble solids, a light colored and minimally condensed lignin, and a dissolved xylose sugar stream, using only a recyclable acid hydrotrope such as maleic acid. More information can be found in the Minireview by J. Zhu et al .